1964
DOI: 10.1084/jem.120.1.105
|View full text |Cite
|
Sign up to set email alerts
|

The Immunological Basis of Acquired Cellular Resistance

Abstract: Infection with certain organisms is often found to produce a high degree of resistance towards other, unrelated organisms (1). The phenomenon is conspicuous whenever the immunising infection is caused b y a facultafive intracellular parasite (2). The latter provokes an immune response with three peculiarities: a consistent association with delayed-type hypersensitivity, a form of acquired resistance that cannot be passively transferred with serum, and a reported change in the antibacterial activity of the host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
377
3
6

Year Published

1966
1966
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 716 publications
(405 citation statements)
references
References 10 publications
15
377
3
6
Order By: Relevance
“…Data has been presented showing that macrophages from sensitized animals react characteristically to specific antigen. Mackaness has reported that macrophages from immunized mice proliferate in vivo when in contact with the sensitizing bacterial antigens and evolve into cells better able to suppress nonspecifically the growth of ingested microorganisms (31). Peritoneal macrophages from sensitized guinea pigs clump and adhere to peritoneal surfaces in vivo when antigen is injected (32).…”
Section: Discussionmentioning
confidence: 99%
“…Data has been presented showing that macrophages from sensitized animals react characteristically to specific antigen. Mackaness has reported that macrophages from immunized mice proliferate in vivo when in contact with the sensitizing bacterial antigens and evolve into cells better able to suppress nonspecifically the growth of ingested microorganisms (31). Peritoneal macrophages from sensitized guinea pigs clump and adhere to peritoneal surfaces in vivo when antigen is injected (32).…”
Section: Discussionmentioning
confidence: 99%
“…Th1 macrophages preferentially produce NO from arginine; Th2 macrophages produce ornithine. PEC from Th1 or Th2 strains of mice were cultured for 48 h, and supernatants were measured for NO 2 Ϫ and amino acids. RPMI 1640 contains 1100 M arginine.…”
Section: Macrophage Tgf-␤1 Production Is Inversely Proportional To Mamentioning
confidence: 99%
“…M acrophages are essential for host defense (1)(2)(3)(4)(5)(6)(7). In primitive organisms, macrophages are the host defense, in that they are responsible for everything from recognition to engulfment to destruction of threats (8).…”
mentioning
confidence: 99%
“…Since Mackaness and colleagues first described classically activated macrophages as major immune effector cells (Mackaness, 1964), considerable knowledge has been gained concerning distinct macrophage populations, with diverse functional roles. The remarkable plasticity of macrophage responses was classified towards two extremes: M1 and M2 macrophages.…”
Section: Distinct Macrophage Phenotypesmentioning
confidence: 99%